Thermography for the conservation of historical art ifacts: the case of the Chinese Buddha in an underground environment - spa, Testo (Archeomatica, 2024)
Thermography is the ideal choice for protecting historical treasures. Using this technique, we are able to identify imperfections that can damage our artifacts, such as water infiltration or mold, invisible to the naked eye. This technology is increasingly widespread as a preventive maintenance method for cultural and artistic heritage throughout the world. Thermography is not a measurement of temperature, but is based on the principles of thermodynamics: each body is characterized by its own thermal emission depending on its surface temperature, which is in turn conditioned by the thermal conductivity and specific heat of each material. In fact, each material has a different capacity to transmit or retain heat. Thermography allows us to investigate and identify internal problems that are not visible to the naked eye and is very useful in various applications for the protection of artistic and cultural heritage.